Language Production and Activity Systems in Pokémon Go: A Content Analysis of In-Game Communication - Ismit Karim (Program Studi Pendidikan Bahasa Inggris, 2026)
Mobile augmented reality (AR) games offer a novel and unexplored context for situated language learning. In these games, players engage in authentic communication influenced by game mechanics, community norms, and shared objectives. This study employs Engeström’s (1987) Activity Theory (AT) framework to analyze language production and learning within the Pokémon Go gaming community. By conducting content analysis of a gameplay vlog and first-person observations of the game application, the study investigates how the six components of the activity system—subject, object, mediating artifacts, rules, community, and division of labor—interact to create conditions for language use and learning. The analysis reveals that language functions as both a mediating artifact and an outcome of participation. Game-specific lexical items emerge from and reinforce the activity system’s structure, while contradictions between components, particularly between game-imposed rules and community-driven knowledge-sharing practices, generate opportunities for language development. These findings contribute to the growing body of research on game-based language learning and extend the application of Activity Theory to mobile AR gaming environments.